Perbandingan Kesantunan Berbahasa Siswa di Lingkungan MAN 2 Kota Padang dan MAN 2 Kabupaten Solok Selatan - Falaakh, Alfian; Aslinda, Aslinda; Revita, Ike (LPPM Institut Pendidikan Nusantara Global, 2024)
This research is a descriptive research with a qualitative approach. Data collection was carried out using the simak method with the technique of simak libat cakap. The data in this study were obtained from the observation process, notes, and recordings. In analyzing the data, the author classifies the data that has been obtained into politeness strategies and principles. The author also uses translational and pragmatic methods. The translational method is used to translate the Minang-language data into Indonesian. The data is presented using informal method in the form of described speech and dialog. The results of the analysis show that 1) students in MAN 2 of Padang City tend to use positive politeness strategies with 64.77% and so do in MAN 2 of South Solok Regency with 56.84%. This is because students at MAN 2 of Padang City and MAN 2 of South Solok Regency both try to be close to their speech partners by using speech that contains positive politeness. 2) the principle of politeness that tends to be used by students in MAN 2 Padang City is the maxim of generosity and acceptance with 37.50% while in MAN 2 South Solok Regency tends to use the principle of politeness with the maxim of aggreement 58.33%. Based on these results, students at MAN 2 of Padang City tend to praise their speech partners and give burden to themselves in speaking, while at MAN 2 of South Solok Regency are more likely to maximize compatibility with their speech partners.